2013
DOI: 10.1097/hco.0b013e32835dd005
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and growth in congenital heart disease

Abstract: Optimizing nutritional intake has been targeted as a key component of the National Pediatric Cardiology Quality Improvement Collaborative. This initiative has enabled the development of best practices that have the potential to mitigate poor growth in children with congenital heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
131
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 40 publications
2
131
0
2
Order By: Relevance
“…Since 95% of the world’s malnourished live in low/middle-income countries,24 congenital heart programmes in resource-limited settings must recognise the impact malnutrition can have on the programme’s outcomes. Optimisation of nutritional intervention before and after surgical correction and standardisation of feeding protocols is vital to achieve the best postoperative care 25. Nurses empowered through the IQIC programme have initiated a nutritional intervention quality improvement initiative following the identification of this risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Since 95% of the world’s malnourished live in low/middle-income countries,24 congenital heart programmes in resource-limited settings must recognise the impact malnutrition can have on the programme’s outcomes. Optimisation of nutritional intervention before and after surgical correction and standardisation of feeding protocols is vital to achieve the best postoperative care 25. Nurses empowered through the IQIC programme have initiated a nutritional intervention quality improvement initiative following the identification of this risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…A European multicenter study in 12 countries reported 7% of the hospitalized children were malnourished upon admission (7). In this and other surveys, rates of malnutrition are higher in association with specific disease conditions including psychiatric disorders, gastrointestinal disease, congenital heart disease, among others (3,7). Notably, many and sometimes most hospitalized malnourished children do not receive nutrition support (5).…”
Section: Prevalencementioning
confidence: 93%
“…These are complex clinical outcomes of which providing good nutrition is but 1 contributor. 7,8,10 For example, Children's Hospital Colorado's Heart Institute does not have a standardized process for gastrostomy tube placement for infants unable to meet their oral intake goals. Approximately 40% of infants with single-ventricle physiology undergo gastrostomy tube placement; and the variability in this practice is felt to greatly affect length of stay.…”
Section: Figurementioning
confidence: 99%
“…Poor caloric and protein delivery and inability or loss of ability to orally feed and breastfeed may contribute to neurodevelopmental and neurocognitive delays as well as to parental frustration, anxiety, and disappointment. [7][8][9][10] Lower than growth velocity than that expected for age and gender is prevalent in infants and children with congenital heart disease and may be due to inadequate nutrition delivery. [11][12][13][14][15] In infants with single-ventricle physiology, providing adequate nutrition can be particularly difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation